Congenital Dermal Sinus: case series and the consequences of late diagnosis and treatment - Alick Durão Moreira (Brazilian Society for Pediatric Neurosurgery, 2020)
Introduction:Congenital Dermal Sinuses (CDS) are rare closed dysraphisms that can present throughout the extent of the neuroaxis. They occur due to a failure of the disjunction of the neuroectoderm and cutaneous ectoderm in a focal point during 3-4 week of embryogenic development. The prevalence of CDS of all types has been estimated to be 1 in 2,500 live births, most commonly localized in the lumbar region. More than half of the cases are associated with dermoid or epidermoid tumors. Clinical presentation of CDS usually consists in cutaneous stigmas like dimples, which has the potential to be diagnosed at birth. However, the majority of patients are diagnosed older and after complications such as meningitis, abscess, osteomyelitis, rupture of an associated epi/dermoid cyst. Once suspected the patient should be submitted to an image study with CT scan and/or MRI, and surgical consultation. Complete exeresis is the definitive treatment. Case report: we present 3 cases of CDS, including an extremely rare case of frontonasal location, to illustrate the extent of the disease and the importance of early diagnosis and treatment. All of the 3 cases presented with complications, requiring surgical treatment and long term antibiotic therapy. Conclusion: Although well reported in the literature, CDS are usually diagnosed after complications. The knowledge of clinical presentation, early diagnosis and treatment are essential to prevent its life threatening complications.